Political Hegemony and Neutrality of Local Media: A Theoretical Study of Post-2024 Election News Practices in West Sulawesi - Sumarni Sumai; Fajar Sidiq; Arifuddin Tike (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This article examines the practice of local media reporting in West Sulawesi after the 2024 General Election through a theoretical approach based on critical discourse analysis. The main focus of this study is to examine the relationship between political interests and media neutrality, and how local media play a role in shaping political legitimacy through hegemonic narratives. Using the framework of Gramsci's hegemony theory, Herman & Chomsky's propaganda model, and agenda setting theory, this article reveals that local media tend to strengthen the dominance of political elites by highlighting narratives of victory and stability without including the voices of the opposition or civil society. The findings show that what appears to be neutral reporting is actually a form of symbolic hegemony that is decentralized and based on local economic-political relations. This article contributes to the development of hegemony theory in the context of local political communication in Indonesia, by offering a concept of how local media actively shape ideological consensus in a fragmented power landscape